Chapter Guidance Specificity in Educational Research. Criticisms and Area of Intervention in Higher Education - Cunti, Antonia (Studies on Adult Learning and Education, 2018)
The purpose of this paper is to discuss and reflect on the Neapolitan section of the PRIN project from a critical perspective. The research underlines the relevance of combining the dimensions of meaning, continuity, and change, giving individuals the chance to try out promising educational itineraries where guidance is understood as a pedagogical tool of higher education contexts